(untitled) (College of Basic Education Research Journal, 2025)
Last decades, nanotechnology technique attracted attention of researchers, it’s considered an important tool in many applications such as healthcare. In this study, Zinc Oxide Nanoparticles (ZnONPs) were used as a parameter for some histological and biochemical changes in male rats. Primary results showed that treated animals with 100 mg/ml on nanoparticles daily showed a response to some histological changes in hepatic and renal tissue. this variation includes characterized degeneration, necrosis, and apoptosis with vascular changes accompanied by inflammatory reactions of hepatic tissue. Regarding histological changes in renal tissue, results showed generation of necrotic changes in epithelium of renal tubules as well as vasculitis , degeneration, and necrosis of the renal corpuscles. Results also displayed an increase in values of Serum acid, Serum creatinine, Serum glutamic oxaloacetic transaminase (GOT), and Alkaline phosphatase in comperes with a control group. however, there was a reduction in values of blood urea and Serum glutamic pyruvic transaminase (GPT) observed in treated animals. In contrast, biochemical results of blood showed an increase in GOT and GPT (serum acid, blood urea, serum creatinine, serum (GOT), serum (GPT), and alkaline phesion. phosotase). Aim of this study was to estimate toxic effect of Concentra.